RELATIONSHIP BETWEEN STUDENTS 'PERCEPTION OF ADIWIYATA PROGRAMSWITH STUDENTS' ENVIRONMENT ATTITUDES IN PRIMARY SCHOOLS - Ririn Indriani; Guslinda (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This research aims to identify: (1) the perception of fifth-grade students regarding the Adiwiyata program at SDN 110 Pekanbaru, (2) the environmental awareness attitudes of fifth-grade students at SDN 110 Pekanbaru, and (3) the correlation between students’ perceptions of the Adiwiyata program and their environmental awareness. This study is categorized as quantitative research with a correlational approach. The sampling technique used was simple random sampling, in which the entire fifth-grade student population at SDN 110 Pekanbaru served as the sample. The data were collected through two questionnaires measuring students’ perceptions of the Adiwiyata program and their environmental awareness attitudes. Statistical analysis was employed to process and interpret the findings. The results indicate that the perception of fifth-grade students regarding the Adiwiyata program falls into the moderate category, with a percentage of 64%. Their environmental awareness also lies at a similar level, reaching 73%. Furthermore, hypothesis testing revealed a strong correlation between students’ perceptions of the Adiwiyata program and their environmental awareness, with a correlation coefficient of 0.636. The significance test showed that the calculated t-value (5.417) was greater than the t-table value (1.68), leading to the rejection of H₀ and acceptance of Hₐ. Thus, it can be concluded that there is a significant correlation between students’ perceptions of the Adiwiyata program and their environmental awareness attitudes at SDN 110 Pekanbaru.